The Italian party : a novel - Lynch, Christina (St. Martin's Press, 2018)
"Newly married [in 1956], Scottie and Michael are seduced by Tuscany's famous beauty. But the secrets they are keeping from each other force them beneath the splendid surface to a more complex view of Italy, America, and each other. When Scottie's Italian teacher--a teenager with secrets of his own--disappears, her search for him leads her to discover other, darker truths about herself, her husband, and her country. Michael's dedication to saving the world from communism crumbles as he begins to see that he is a pawn in a much different game"--Amazon.com.